Knee confidence in youth and young adults at risk of post-traumatic osteoarthritis 3–10 years following intra-articular knee injury. Issue 7 (July 2018) - Ezzat, A.M.; Whittaker, J.L.; Toomey, C.; Doyle-Baker, P.K.; Brussoni, M.; Emery, C.A.
Abstract: Objectives: To examine differences in knee confidence between individuals with a history of youth sport-related knee injury and uninjured controls. Design: Historical cohort study. Methods: Participants include 100 individuals who sustained a youth sport-related intra-articular knee injury 3–10 years previously and 100 age-, sex- and sport-matched uninjured controls. Outcomes included: Knee confidence (Knee Osteoarthritis and Outcome Score); fat mass index (FMI; dual-energy X-ray absorptiometry); and weekly physical activity (modified Godin–Shephard Leisure Time Questionnaire). Mean within-pair differences (95% CI) were calculated for all outcomes. Unadjusted and adjusted (FMI and physical activity) conditional (matched-design) logistic regression (OR 95% CI) examined the association between injury history and knee confidence. Results: Median age of participants was 22 years (range 15–26) and median age at injury was 16 years (range 9–18). Forty-nine percent (95% CI; 39.0, 59.0) of previously injured participants were bothered by knee confidence, compared to 12% (5.5, 18.5) of uninjured participants. Although there was no between group difference in physical activity, injured participants had higher FMI compared to controls (within-pair difference; (95% CI): 1.05 kg/m 2 ; (0.53, 1.57)). Logistic regression revealed that injured participants had 5.0 (unadjusted OR; 95% CI; 2.4, 10.2) and 7.5 times (adjusted OR; 95% CI: 2.7, 21.1) greater odds of being bothered by knee confidence than controls. Conclusions: Knee confidence differs between individuals with a previous youth sport-related knee injury and healthy controls. Knee confidence may be an important consideration for evaluating osteoarthritis risk after knee injury and developing secondary prevention strategies.